Quantitative failure analysis for static electricity-related explosion and fire accidents on tanker vessels under fuzzy bow-tie CREAM approach. (January 2022) - Elidolu, Gizem; Akyuz, Emre; Arslan, Ozcan; Arslanoğlu, Yasin
Highlights: A quantified risk-based analysis is performed to enhance operational safety. Systematic failure analysis under bow-tie and CREAM approach. Fuzzy logic is adopted to deal with vagueness and ambiguity. Abstract: Cargo operations on tanker vessels involve high risks to crew and the marine environment. At the time of loading and unloading of cargoes and tank cleaning operations, consequences of accidents may be severe such as loss of lives, property loss and marine pollution. One of the most critical accidents is an explosion which may advance to a large fire. An explosion may occur due to flammable and combustible materials, electric arcs, dangerous operations, like hot work on deck, or static electricity. This study focuses on the issue of static electricity, which is one of the serious threats onboard and can cause large explosions under hazardous conditions if a discharge is in contact with nearby flammable gases or air mixture. In a bow-tie structure, static electricity-related explosion and fire accident was determined as the top event. In the fault tree diagram, intermediate events were considered as the flammable atmosphere in a tank, operational failures, technical failures, and unsafe practices which cover direct human errors. Fuzzy logic and Cognitive Reliability and Error Analysis Method (CREAM) were used for quantitative failure analysis, and the probability of accident risk was found as 6.31E-02. Findings show that the most critical contributions to the top event are minimal cut sets of lack of monitoring cargo tank atmosphere, inadequate actions for reducing the O2 level in tank, failure to understand safety data sheets, failure to follow procedures, non-bonded ullage & sample apparatus. The research provides a significant contribution to the literature and gives information regarding static electricity risks to ship officers, tanker safety superintendents and other maritime authorities to improve the safety of cargo operations.